IMPLEMENTASI METODE QIRA’AH DALAM PEMBELAJARAN BAHASA ARAB DI MADRASAH HIDAYATUL MUBTADIIN LIRBOYO KEDIRI - Huda, Moh Nurul; Nurrosyid, Ahmad Faiz; Aji, Akhmad Bayu (Al-Fakkaar, 2024)
Reading is one of the basic skills that allows learners to access information, understand texts, and expand vocabulary. Effective learning of Arabic requires a focus on developing reading skills to ensure a good understanding of classical texts, literature, and other sources. This research explores the implementation of the qiro'ah method in Arabic language learning at Madrasah Hidayatul Mubtadiin. The results of the research show that this qiro'ah teaching method has a positive impact on students' reading abilities, not only in technical terms, but also understanding in learning Arabic. Researchers used three data collection techniques, namely interviews, observation and documentation. In the interview technique, the researcher interviewed mudir and santri regarding the process of implementing the qiro'ah method in learning Arabic at the Hidayatul Mubtadiin Madrasah Lirboyo Kediri. In the observation technique, the researcher came directly to the Hidayatul Mubtadiin Islamic boarding school and then saw and observed the Arabic language learning process using the qiro'ah method. To strengthen the results of observations and interviews, researchers also quoted information from literary sources that were relevant to this research. After all the data is collected it is then analyzed. The data analysis that the researcher carried out was by taking notes and detailing the data from observations, interviews and documentation on learning activities at Madrahas Hidayatul Mubtadiin Lirboyo Kediri.